Literature Review: The Effect of Acupressure on Menstrual Pain in Adolescents - Niken Firda; Kiswati Kiswati; Ira Titisari; Finta Isti Kundarti (Journal of Ners and Midwifery, 2022)
Menstrual pain is a condition that bothers most women regardless of age, with the highest percentage being in their teens. Menstrual pain is categorized into mild, moderate, severe and very severe pain. Women who experience menstrual pain can interfere with their activities ranging from daily activities, school to work. One way to reduce menstrual pain non-pharmacologically is to use acupressure. This study aimed to determine the effect of acupressure on menstrual pain in adolescents. This was a literature Review with Systematic Mapping Study (Scoping Study) design. This study used journals published in the last 5 years. The ten journals used were obtained from the Google Schoolar, PubMed and Sciencedirect databases. The journals obtained had passed the selection based on the year of publication, the suitability of the title with keywords, the feasibility of the journal, the ability to access, duplication and inclusion criteria. The journal was then analyzed using the instrument of presenting the results of a literature review. The most widely used acupressure point was sanyinjiao (Sp 6) by pressing or massaging. The intensity of menstrual pain after being given acupressure was decreased, the average pain intensity decreased between before and after being given acupressure starting from a scale of 0.86 to 6.7. The results of the analysis of all journals show P value < a, which meant that there was a significant effect of giving acupressure on decreasing the intensity of menstrual pain in adolescents. Giving acupressure by pressing or massaging certain meridians can increase the levels of endorphins that are useful for reducing the intensity of menstrual pain in adolescents. Education about proper massage techniques will help reduce the level of pain that occurs during menstruation.